2022
DOI: 10.21608/ejhc.2022.252329
|View full text |Cite
|
Sign up to set email alerts
|

Mothers Health Awareness Toward Their Children Undergoing Congenital Heart Surgery

Abstract: Background: Congenital heart defect is the second cause of death in infancy and childhood and is the leading cause of childhood morbidity and mortality. congenital heart surgery corrects heart defect that a child is born with it, enhance mothers knowledge and practices toward their children undergoing congenital heart surgery help child to recover early and prevent complication. Aim: this study aimed to assess mothers' knowledge and reported practices toward their children undergoing congenital heart surgery S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…This study result was consistent with [13] who studied "Mothers' care for their infants with congenital heart anomalies" and reported that 71% of the studied mothers' total practices were satisfactory. However, the findings of this study were disagreed with [19] who reported that 91.4% of total mothers' practice was unsatisfactory. This might be related to family education system in the hospital which is responsible for providing regular teaching for mothers with children after open heart surgery and ensuring the mothers have gained the necessary skills needed for caring for their children at home.…”
Section: Discussioncontrasting
confidence: 99%
“…This study result was consistent with [13] who studied "Mothers' care for their infants with congenital heart anomalies" and reported that 71% of the studied mothers' total practices were satisfactory. However, the findings of this study were disagreed with [19] who reported that 91.4% of total mothers' practice was unsatisfactory. This might be related to family education system in the hospital which is responsible for providing regular teaching for mothers with children after open heart surgery and ensuring the mothers have gained the necessary skills needed for caring for their children at home.…”
Section: Discussioncontrasting
confidence: 99%